If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = -1(x + 3) * 2 + 1 Multiply f * x fx = -1(x + 3) * 2 + 1 Reorder the terms: fx = -1(3 + x) * 2 + 1 Reorder the terms for easier multiplication: fx = -1 * 2(3 + x) + 1 Multiply -1 * 2 fx = -2(3 + x) + 1 fx = (3 * -2 + x * -2) + 1 fx = (-6 + -2x) + 1 Reorder the terms: fx = -6 + 1 + -2x Combine like terms: -6 + 1 = -5 fx = -5 + -2x Solving fx = -5 + -2x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = -5x-1 + -2 Simplifying f = -5x-1 + -2 Reorder the terms: f = -2 + -5x-1
| 3[x-4]=-4x+37 | | Y-1/6=-4/5 | | W/4-2=12x4 | | -3y+1(-9y-3)=-8+2(6-y) | | 11=3x+-25 | | 4(x+4)+2x=52 | | 30+5(x-3)=4(x+2)+3x | | 180+180(.1667)= | | 32-11=3(x-2) | | 22x+3600=34x | | (xy^3+1)dx+(x^2y^2)dy=0 | | 60=3x-15 | | 2[x-1]+50=-4x | | 7x+1x=17x-1+9x | | log(22-x)=-1+logx | | 41=39-5(2-2w) | | 22+2y-6=11y-14-3y | | 0.15m-20=80 | | 29+4b=6b+2 | | 5x-6x=6x+7 | | 27=35-7(-1-3w) | | 20-0.15m=80 | | 4x=8x+42 | | 15=z/-2 | | X+19+3x=-8-3x-15 | | x=-16-12x | | 4-y=3(-2) | | 28=20-5(-5-1w) | | 5x+4p=7 | | 2x+5.7=-8.3 | | 24x+4500=33x | | 2y+5y+y= |